An unusual cause for chronic pain in the proximal hamstring (buttock) area - Vad, V. (2000)
Hamstring injuries are common in tennis. However, there is a sub-group of tennis players who maybe have a different aetiology of chronic hamstring pain at the muscle-tendon junction. A summary of 12 cases is presented below. All 12 were collegiate tennis players aged 20-22, who presented for a second opinion following extensive rehabilitation (minimum 4 months) for a presumed chronic hamstring strain. The case histories showed the following characteristics for all of the players. They noted the onset of pain while lunging for a stroke, with the onset of hamstring pain on the ipsilateral side of their dominant arm. None had any low back or buttock pain. The pain at the muscle-tendon junction of the hamstring worsened with continued lunging as well as with bending and prolonged sitting. Physical examination showed only mild to moderate pain reproduction with deep palpation, as well as with resisted hamstring manual muscle testing. The patients had L5 myotome weakness. MRI of the lumbar spine was ordered to rule out the lumbar spine as the aetiology of the chronic hamstring pain. MRI showed an L4-L5 disc bulge without any nerve root compression. The results of nerve conduction studies were normal, but the needle examination revealed spontaneous activity at the L5 myotome of the symptomatic limb. At this point, the players had a series of L5 selective nerve root epidural injections (Ref. 1) performed under fluoroscopy (average of 1.4 injections, range of 1-3). This was combined with daily use at night of a back cryobrace combined with a 5-stage lumbar stabilisation programme using aqua-therapy (Ref. 2). At an average of eight weeks after the first injection, all players returned to pre-injury level of tennis competition. Chemical radiculitis `Chronic hamstring strain` is actually a chemical radiculitis from an L4-L5 disc bulge. The chemical irritation of the nerve root from the disc nucleus pulposus can manifest itself only at the muscle-tendon junction at times without any back or buttock pain. Increased pain with prolonged sitting can also lead to a suspicion of a disc causing nerve root irritation. The transforaminal epidural injections under fluoroscopy, which are a much more precise form of the old epidural technique, have the advantage of precisely delivering the medication at the nerve-disc interphase where the pathology lies, while minimising nerve root injury or dural puncture incidence. These more exotic epidurals produced a 75% success rate in a retrospective study and 84% success rate in a prospective study at our institution, with long-lasting relief of pain when combined with a precise rehabilitation program. The goal of rehabilitation is to gradually restore the delicate balance between flexibility, strength and endurance. The rehabilitation programme is carried out in four phases. In the early stages of phase1, aqua-therapy is used in combination with isometric strengthening and stretching. Phase 2 emphasises non-weight bearing, concentric strengthening. Phase 3 emphasises functional weight-bearing eccentric strengthening. The last phase, Phase 4, focuses on sports-specific training.